1964
DOI: 10.1016/s0006-3495(64)86776-x
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Structural Basis for the Excitation Properties of Axons

Abstract: A structural model is suggested for axon membranes consisting of a double layer of lipid and phospholipid molecules in which the polar ends of certain phospholipids change their orientation and combining properties under the influence of an electric field. The phosphate groups act as ion exchange "gates" for the control of ion flow through the membrane. Expressions are developed for the calculation of membrane current components as functions of time, potential, and ionic environment. Approximate solutions show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

1965
1965
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(50 citation statements)
references
References 9 publications
4
46
0
Order By: Relevance
“…It is reasonable to assume that this gate is open at the outer surface of the nerve membrane in view of the insolubility of T T X in lipids. The gate is probably controlled by membrane potential and calcium (Goldman, 1964). High external calcium concentration has been shown to interact with the blocking action of T T X (Takata et al, 1966), and this is consistent with the above mentioned notion.…”
Section: The M a X I M U M Values F O R T H E Early T R A N S I E N Tsupporting
confidence: 81%
“…It is reasonable to assume that this gate is open at the outer surface of the nerve membrane in view of the insolubility of T T X in lipids. The gate is probably controlled by membrane potential and calcium (Goldman, 1964). High external calcium concentration has been shown to interact with the blocking action of T T X (Takata et al, 1966), and this is consistent with the above mentioned notion.…”
Section: The M a X I M U M Values F O R T H E Early T R A N S I E N Tsupporting
confidence: 81%
“…2), it appeared to be the trivalent cation most likely not to bind at all to the axonal membrane.) The calculation of the approximate density of surface charges on the membrane is achieved through use of the (0) (Goldman, 1964;D'Arrigo, 1972) that the axonal membrane in the region surrounding a sodium 'gate' is essentially represented by a phospholipid bilayer. At the same time, the agreement provides indirect support for those theories (Goldman, 1964;Wang, 1970;Wei, 1971;D'Arrigo, 1972) which ascribe the voltage-dependent, sodium 'gating' function to the polar complexes of membrane phospholipids, although most of these proposals have been shown to contain serious inadequacies (D'Arrigo, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of the approximate density of surface charges on the membrane is achieved through use of the (0) (Goldman, 1964;D'Arrigo, 1972) that the axonal membrane in the region surrounding a sodium 'gate' is essentially represented by a phospholipid bilayer. At the same time, the agreement provides indirect support for those theories (Goldman, 1964;Wang, 1970;Wei, 1971;D'Arrigo, 1972) which ascribe the voltage-dependent, sodium 'gating' function to the polar complexes of membrane phospholipids, although most of these proposals have been shown to contain serious inadequacies (D'Arrigo, 1972). In consideration of the number of electrophysiological and pharmacological properties common to most axons (see Hille, 1970;D'Arrigo, 1972), it seems improbable that the axonal membrane is structured very differently in different types of axons.…”
Section: Discussionmentioning
confidence: 99%
“…Tasaki (1968) suggested that it would seem reasonable to regard any pores that might exist in the membrane as dynamic, time dependent structures, rather than as rigid, static holes. Goldman (1964) also felt that it was highly unlikely that individual channels for the ions are established by any rigid structure. He felt that the phosphate groups of the membrane act as exchange sites through which the ions pass as they rush through the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…He suggested that initiation of an active response occurred when the ratio of divalent ions to univalent ions in the cell membrane was reduced to a critical value. Goldman (1964) theorized that the calcium ions could corrbine with the exchange sites and form an area having the characteristic of low conductance for specific ions. He felt that changes in the electric field and thermal agitation could modify the binding properties of the phosphate groups at the ex change sites causing a change in the characteristics of the membrane.…”
Section: Resultsmentioning
confidence: 99%